By-catch of sea turtles in Pacific artisanal fishery: Two points of view: From observer and fishers - Carpio, Antonio José; Álvarez, Yamel; Serrano, Rocio; Vergara, M. Belen; Quintero, Erklin; Tortosa, Francisco S.; Rivas, Marga L. (Frontiers in Marine Science, 2022)
Fisheries bycatch is a primary driver of population declines in marine megafauna. These captures not only have environmental impacts, they also have economic consequences for fishers such as direct losses when repairing fishing gear. Therefore, evaluating the fishers’ perception of bycatch and comparing it with data from scientific fisheries observers might provide a broader view of the current situation these species face. To do this, we obtained data concerning the bycatch of 1,838 sea turtles between 2008-2018 in the Eastern Pacific Ocean as well as informative surveys from 421 artisanal fishers surveyed in 2020. There is a discrepancy between the bycatch observed and the fishers’ perceptions of it. The observers’ results identified that high rates of incidental capture of sea turtles are associated with the mahi mahi fishery that occurs during winter and is a shallow set fishery using fish as bait. The olive ridley turtle was the main species affected by bycatch. According to the fishers’ perception, bycatch was higher with the use of J-hooks and a longline (compared to circle hooks and to gill nets and trawl nets) and when the target species are pelagic fish during the winter season. In addition, the fishers’ perception showed that 39.4% considered incidental fishing as an environmental problem and 28.5% considered it as a nuisance, while 32.1% do not consider sea turtle bycatch as a problem. These findings suggest that 60% of fishers do not consider it a need to protect sea turtles. Given the different responses between fisheries observers and fishers’ perception, it is clear that more dialogue is necessary to raise awareness about the effects of bycatch on worldwide sea turtle populations. Thus, there is an enormous potential to recruit/increase fishers’ active participation for turtle protection. In this context, the idea of including the fishers’ perception into any management strategy or conservation measure should be reinforced in order to effectively reduce the bycatch of these iconic species.